PEMBERDAYAAN KELOMPOK TANI MAJU BERSAMA MELALUI BUDIDAYA TANAMAN HORTIKULTURA DAN PEMBUATAN PUPUK ORGANIK DI KABUPATEN KOLAKA TIMUR - Harudin, La; La Oge; Wa Ode Umrawati Latif; La Ode Santiaji Bande; Muhammad Amrullah Pagala; Deki Zulkarnain; La Ode Muh. Munadi; Yamin Yaddi; La Ode Sahaba (Yayasan Baitul Hikmah al-Zain, 2025)
Empowering farmers in Kolaka Timur Regency through horticultural crop cultivation and organic fertilizer production aims to enhance farmers' knowledge and skills in managing agriculture more efficiently and sustainably. This community service program involves the Maju Bersama Farmers Group as the main subject and is implemented using a participatory approach, where farmers are directly involved in planning, training, and field mentoring. The activities carried out include training on modern horticultural cultivation techniques, organic fertilizer production, and ongoing field mentoring. The results of the program show an increase in farmers' knowledge regarding efficient farming techniques, as well as heightened awareness of the importance of using organic fertilizers. Furthermore, social changes occurred, including the emergence of local leaders who inspire other farmers and the formation of new practices within the agricultural system. This program successfully increased agricultural productivity and farmers' well-being in Kolaka Timur Regency, while also contributing to the development of sustainable agriculture